Irrigational Requirements of Wheat Crop in India— A Review - Pande, R.C. (Journal of Soil and Water Conservation, 2022)
Next to Paddy, wheat, is an important grain crop of India, grown in 13.5 million ha. of land with a total production of 12.07 million tons per annum. Wheat is grown in 67 percent of the area on stored soil moisture and this is not sufficient to meet out the optimum require- ment for optimum yield. Judicious use of irrigation water, is therefore, essential in order to provide optimum conditions for growth, deve- lopment and yield of crop. The work done on irrigational requirements of wheat has been reviewed in order to draw a guide line for preparing an irrigational schedule of wheat crop for obtaining optimum economic yields.